Comparative Cytogenetic Analysis of the Genus Symphysodon (Discus Fishes, Cichlidae): Chromosomal Characteristics of Retrotransposons and Minor Ribosomal DNA - Gross, M. C.; Schneider, C. H.; Valente, G. T. [UNESP]; Porto, J. I. R.; Martins, C. [UNESP]; Feldberg, E. (Karger, 2009)
As part of a genetic screening program for wild Discus fishes, we analyzed karyotypes and cytogenetic characteristics of Symphysodon aequifasciatus, S. discus and S. haraldi using C-banding and fluorescent in situ hybridization ( FISH) with the Rex3 retrotransposon and 5S rDNA probes in mitotic and meiotic chromosomes. In the 3 species, diploid chromosome number was 2n = 60 and karyotypes contained predominantly meta-submetacentric chromosomes. C-banding showed blocks of constitutive heterochromatin mainly in the pericentromeric region. Physical mapping of repetitive 5S rDNA sequences and Rex3 retrotransposons in mitotic and meiotic chromosomes showed partial colocalization of constitutive heterochromatin and repetitive elements. Correlations among the accumulation of repetitive elements, heterochromatinization and chromosome rearrangements have been hypothesized to explain the karyo-type differentiation in the Symphysodon genus. The role of repetitive elements in adaptation to highly diverse habitats, as well as in the generation of the phenotypic and genetic variability found in wild Discus populations, needs to be further investigated. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Fluorescent in situ hybridization; Heterochromatin; Meiosis; Mitosis; 5S rDNA; Rex3